Determinants of default from completion of child immunization among children aged 15–23 months in Kacha Bira district, Kembata Tembaro zone, South Ethiopia: a case–control study - Masebo, Sitota Tesema; Wolka, Eskinder; Kussa, Sintayehu; Uloro, Muluken Markos; Handiso, Selamu Abera; Libabo, Dilugeta Mathewos; Anjajo, Eyosiyas Abreham; Bogino, Efa Ambaw (Frontiers in Public Health, 2024)
Background: Child immunization is crucial to protect children from vaccine-preventable diseases. However, if a child defaults from completing immunization, they are at a greater risk of contracting such diseases. Previous studies have evaluated various factors that contribute to defaulting from immunization, but they did not consider the fear of COVID-19 as a variable.Additionally, there is inconsistency in the factors identified across different areas. This study aims to examine the determinants of defaulting from child immunization among children aged 15-23 months in Kacha Birra district, Kembata Tembaro zone, South Ethiopia.Methods-A study was conducted using a community-based unmatched case-control design to identify the determinants of child immunization completion. The study selected 255 children aged 15-23 months in the Kacha Birra district from May 3 to June 1, 2022, using a multi-stage sampling technique. Face-to-face interviews of mothers or immediate caretakers of the child were conducted using a mobile device, and the questionnaire was developed using the Kobo Toolbox. The data collected was analyzed using SPSS model 25. Multivariable logistic regression was used to identify the determinants, and the adjusted odds ratio with 95% CI and p-value<0.05 was used to declare statistical significance.-Multivariable logistic regression analysis identified four independent predictors of immunization defaulting. ANC follow-up [AOR = 5.40, 95% CI (2.24-13.52)], Postponing vaccination schedule [AOR = 2.28, 95% CI: (1.05-4.93)], Parity of the mother [AOR = 3.25, 95% CI: (1.45-7.27)] and Knowledge of the mother about vaccination [AOR = 6.77, 95% CI: (2.33-19.64)] were determinants of immunization defaulting.-In this study, lack of ANC follow-up, postponement of the vaccination schedule, mothers with parity of greater than four, and poor knowledge of the mothers about immunization were identified as determinants of immunization defaulting.